2020
DOI: 10.1177/1368430220932636
|View full text |Cite
|
Sign up to set email alerts
|

Interracial contact at work: Does workplace diversity reduce bias?

Abstract: Research suggests that anti-Black bias among White Americans is persistent, pervasive, and has powerful negative effects on the lives of both Black and White Americans. Research also suggests that intergroup contact in workplaces can reduce bias. We seek to address two limitations in prior research. First, the workplaces reviewed in prior studies may not be typical. Second, previously observed relationships between workplace contact and bias may stem from selection bias—namely, that White individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The results indicated that openness and verbal ability predicted positive attitudes toward workplace diversity, and that power and security are less associated [42]. A study performed in the USA regarding 3359 employees determined that working with employees from two different races showed that intergroup contact reduces the adverse effects for both races and improves co-working, performance, and acceptance [54]. A study performed in South Africa and included employees from financial institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that openness and verbal ability predicted positive attitudes toward workplace diversity, and that power and security are less associated [42]. A study performed in the USA regarding 3359 employees determined that working with employees from two different races showed that intergroup contact reduces the adverse effects for both races and improves co-working, performance, and acceptance [54]. A study performed in South Africa and included employees from financial institutions.…”
Section: Discussionmentioning
confidence: 99%
“…While in the past diversity could also have the disadvantage of reducing the work teams' efficiency due to the differences in the way individuals interact, employee hostility, or communication difficulties [51], now, in a world where the population of racial minorities is growing, women have different employment roles, diversity influences learning, intergroup behaviors, and social relationships, based on "us" not "they", changing the optics and eliminating the idea of local employees, instead labeling them "global talents" [52][53][54][55], civic and organizational involvement [56], as well as workplace relations [57], innovation, financial performance [58], employment based on ethical principles [59], the existence of several talented candidates, a better customer relationship, the adoption of better decisions [60], the improvement of employees' physical and mental health [61], the improvement of productivity, support for disability issues, the improvement of workplace attractiveness [62], the increase of employee welfare [63], the improvement of perceptions through the efficient communication and settlement of diversity issues, and the reduction of adverse effects by reducing the resistance of those employees who feel threatened by diversity [64,65] based on a solid corporate culture and social responsibility principles. According to the authors' arguments, as employees and managers are open to communicating, having intergroup activities, and relating socially and economically, they will more easily accept a workplace based on diversity, and the company will achieve its development.…”
Section: Hypothesis 3 (H3) Workplace Diversity Is Positively Related ...mentioning
confidence: 99%
“…The Research Topic also aims to draw scholars and policy makers' attention to well-researched, yet largely overlooked, social psychological theories. Areas that have not been fully embraced include contact theory (e.g., Darling-Hammond et al, 2021;White et al, 2021) and social identity processes, especially with respect to discrimination, prejudice, and intergroup conflict and co-operation (Tajfel and Turner, 1979;Turner et al, 1987;Turner and Reynolds, 2012). A central idea is that people can define themselves in terms of their social identity as a group member ("we" and "us") which emerges in comparison to other groups.…”
Section: Social Cohesion: a Social Psychological Approachmentioning
confidence: 99%